2004
DOI: 10.1007/978-3-540-24627-5_11
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Complexity of Updates for a Class of Database Views

Abstract: Abstract. It is well known that the complexity of testing the correctness of an arbitrary update to a database view can be far greater than the complexity of testing a corresponding update to the main schema. However, views are generally managed according to some protocol which limits the admissible updates to a subset of all possible changes. The question thus arises as to whether there is a more tractable relationship between these two complexities in the presence of such a protocol. In this paper, this ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…A fundamental condition in the study of view updates,as reported in [Heg02], [Heg04a], and [Heg04b], is that the update strategies should be closed. The formal definition of an update strategy, and the list of conditions which render it closed, are quite technical and are not needed to understand the work reported here.…”
Section: The Classical Results In the Set-based Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…A fundamental condition in the study of view updates,as reported in [Heg02], [Heg04a], and [Heg04b], is that the update strategies should be closed. The formal definition of an update strategy, and the list of conditions which render it closed, are quite technical and are not needed to understand the work reported here.…”
Section: The Classical Results In the Set-based Frameworkmentioning
confidence: 99%
“…Although it has much in common with the earlier work [Heg04b], it differs in a very fundamental way. Specifically, in [Heg04b], the starting point was the so-called semantic schemata -those which include only the databases which satisfy the constraints of the schema.…”
Section: Pf-schemata and Pf-viewsmentioning
confidence: 91%
See 3 more Smart Citations